2013
DOI: 10.1007/s11856-013-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

On the rate of convergence of Krasnosel’skiĭ-Mann iterations and their connection with sums of Bernoullis

Abstract: In this paper we establish an estimate for the rate of convergence of the Krasnosel'skiǐ-Mann iteration for computing fixed points of nonexpansive maps. Our main result settles the Baillon-Bruck conjecture [3] on the asymptotic regularity of this iteration. The proof proceeds by establishing a connection between these iterates and a stochastic process involving sums of non-homogeneous Bernoulli trials. We also exploit a new Hoeffding-type inequality to majorize the expected value of a convex function of these … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 26 publications
5
65
0
1
Order By: Relevance
“…Regarding the second case, notice that if T t is contractive then F t is contractive; however, the converse is not necessarily true. We start by outlining the following standard assumptions [1], [7].…”
Section: Convergencementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the second case, notice that if T t is contractive then F t is contractive; however, the converse is not necessarily true. We start by outlining the following standard assumptions [1], [7].…”
Section: Convergencementioning
confidence: 99%
“…Funds for A. Bernstein were provided by ARPA-e NODES. constant value of λ k = λ as an example, one has that the average fixed-point residual of the map T after K iterations can be bounded as [1], [7]:…”
Section: Introduction and Problem Formulationmentioning
confidence: 99%
“…where ǫ k is the error of approximating T (x k ), and {α k } k∈N ∈ [0, 1] is a sequence of relaxation parameters. When ǫ k ≡ 0 for all k ∈ N, (7) reduces to the classical KM iteration [20], [22]. It has been shown that the (inexact) KM iteration converges Assumption 1 (Graph Connectivity and Weights Rule).…”
Section: Preliminaries and Problem Statementmentioning
confidence: 99%
“…Remark 1. It is worth pointing out that it is in general standard to leverage T (x) − x as a measure of the convergence speed for the centralized (inexact) KM iteration, since T (x) − x = 0 amounts to T (x) = x, see [20]- [25]. This is why F i (x i,k l ) − x i,k l is employed for measuring the convergence rate of the D-IKM iteration, as shown in (12).…”
Section: The D-ikm Iterationmentioning
confidence: 99%
See 1 more Smart Citation